ИСПОЛЬЗОВАНИЕ ОБРАЗОВАТЕЛЬНОГО ПРОЕКТА ПРИ ИЗУЧЕНИИ АНГЛИЙСКОГО ЯЗЫКА - Каллибекова, М.; Искендеров, Т. (SCIENCE and SOCIETY, 2017)
The article is devoted to the issues of using the educational project in teaching English, the study of advantages and disadvantages of the project work. The author of the article also studies the role of the teacher in using the method of projects in teaching English.
Keywords: project; advantages; disadvantages; method; language; information; English; organization; technology; self education; self control; self assessment; activity